ON THE PUBLICATIONS OF THE COLLECTION “NATIONAL POEMS FOR NATIONAL SONGS” BY HAMZA HAKIMZODA NIYOZIY - Jorayeva Fotima Sharif qizi (TADQIQOTLAR, 2026)
This article analyzes the thematic scope and genre characteristics of the poems included in Hamza Hakimzoda Niyoziy’s collection “National Poems for National Songs.” In addition, the study discusses the sources of the poems included in the 1980 edition of the “Complete Works”, as well as the manuscript and lithographic copies and their publication features.